2022
DOI: 10.5194/acp-2022-755
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The evolution of deep convective systems and their associated cirrus outflows

Abstract: Abstract. Tropical deep convective clouds, particularly their large cirrus outflows, play an important role in modulating the energy balance of the Earth’s atmosphere. Whilst the cores of these deep convective clouds have a significant shortwave (SW) cooling effect, they dissipate quickly. Conversely, the thin cirrus that flow from these cores can persist for days after the core has dissipated, reaching hundreds of kilometers in extent. These thin cirrus have a potential for large warming in the tropics. Under… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…However, both the cloud fraction and the LWP contribute to the higher albedo in the weak-MCAO/high-AOD cases. Previous work has shown that in relatively clean conditions, as the aerosol load increases, less stable conditions typically have a higher LWP than stable conditions (Murray-Watson and Gryspeerdt, 2022), potentially explaining the difference in LWP response between strong and weak events in Fig. 9c.…”
Section: Stability-dependent Aerosol Effectmentioning
confidence: 83%
“…However, both the cloud fraction and the LWP contribute to the higher albedo in the weak-MCAO/high-AOD cases. Previous work has shown that in relatively clean conditions, as the aerosol load increases, less stable conditions typically have a higher LWP than stable conditions (Murray-Watson and Gryspeerdt, 2022), potentially explaining the difference in LWP response between strong and weak events in Fig. 9c.…”
Section: Stability-dependent Aerosol Effectmentioning
confidence: 83%
“…This work uses Lagrangian trajectories to study the temporal evolution of the cloud phase in cold air outbreaks. Detailed discussion of the trajectory generation is described in Murray-Watson et al (2023), which in turn is adapted from Horner and Gryspeerdt (2022). In summary, hourly ERA5 (ECMWF Reanalysis v5; Hersbach et al 2020) 1000 hPa wind data are used to advect pixels forward through time.…”
Section: Calculating "Time Since Ice"mentioning
confidence: 99%
“…Examples of the trajectories generated by this method are shown in Figure 4. The advection procedure is adapted from Horner and Gryspeerdt (2022), which focuses on trajectories starting from points of new convection. Here, a similar method is used, but the initial points are identified as cases where the air has moved from being over sea ice to being over open ocean between time steps of one hour.…”
Section: Trajectory Generationmentioning
confidence: 99%